Derivation and elimination of uremic toxins from kidney-gut axis - Xu, Ying; Bi, Wen-Di; Shi, Yu-Xuan; Liang, Xin-Rui; Wang, Hai-Yan; Lai, Xue-Li; Bian, Xiao-Lu; Guo, Zhi-Yong (Frontiers in Physiology, 2023)
Uremic toxins are chemicals, organic or inorganic, that accumulate in the body fluids of individuals with acute or chronic kidney disease and impaired renal function. More than 130 uremic solutions are included in the most comprehensive reviews to date by the European Uremic Toxins Work Group, and novel investigations are ongoing to increase this number. Although approaches to remove uremic toxins have emerged, recalcitrant toxins that injure the human body remain a difficult problem. Herein, we review the derivation and elimination of uremic toxins, outline kidney-gut axis function and relative toxin removal methods, and elucidate promising approaches to effectively remove toxins.